Neurological outcomes of out-of-hospital cardiac arrest occurring in Tokyo train and subway stations - J. Miyako (Elsevier, 2021)
Objectives: The purpose of this study was to identify a relationship between the background environment, bystander and emergency medical services intervention, and favourable neurological outcomes (CPC1-2) one-month after out-of-hospital cardiac arrest (OHCA) occurred at Tokyo train and subway stations. Methods: This retrospective observational study used OHCA data between 2014 and 2018 that occurred at train stations in Tokyo. The eligible 954 patients were analysed for correlation between background, time frame, and location. Multivariable logistic regression models were used to estimate factors associated with CPC1-2 in patients with cardiogenic OHCA. Results: A total of 886 OHCA cases, cardiogenic (n=562) and non-cardiogenic (n=324), met the inclusion criteria. Of the cardiogenic cases, 71.9% occurred at the platform and on-a-train. One-month CPC1-2 was achieved in 32.0% of cardiogenic OHCAs, which included 47.3% during morning rush hour, 24.7% during daytime hours, 40.2% during evening rush hour, and 20.5% during night-time/early morning hours. CPC1-2 had significant correlation with morning rush hour (adjusted odds ratio [AOR],4.52; 95% confidence interval [CI], 1.09–18.78), evening rush hour (AOR, 6.85; 95% CI, 1.51–31.15), public access defibrillation (AOR, 5.19; 95% CI, 1.38–19.51), and ventricular fibrillation or pulseless ventricular tachycardia (AOR, 7.56; 95% CI, 1.35–42.43). Conclusion: A total of 71.9% of cardiogenic OHCAs occurred at platforms and on trains. To improve neurological outcomes of OHCAs at stations, AED installations on train platforms are necessary. Additionally, using artificial intelligence-based platform monitoring for early detection of OHCAs and offering CPR training are required.